Long-Term Variability on Suspended Particulate Matter Loads From the Tributaries of the World’s Largest Choked Lagoon - Bortolin, Eduardo C.; Távora, Juliana; Fernandes, Elisa H. L. (Frontiers in Marine Science, 2022)
Continental freshwater contributions are the main long-term control on the variability of suspended particulate matter (SPM) concentrations in choked lagoons. The current work aims to assess the seasonal to interdecadal variability in SPM concentrations from Patos Lagoon tributaries, as a case study towards the understanding of tributaries contributions to coastal lagoons. Thus, an interdecadal dataset (1984-2020) was collected in the region of the tributaries of Patos Lagoon (southern Brazil), integrating Landsat series (653 scenes) and in-situ measurements. SPM concentrations were estimated using a semi-analytical multiwavelength algorithm, applied in the regions of the lower course of the tributaries. Results identified SPM concentrations variability in seasonal scales, enhanced by El Niño Southern Oscillation (ENSO) in interannual time scales, influencing in interdecadal trends. The seasonal SPM concentration variability reached 50 g.m-3 to each tributary. The higher SPM concentration values occurred from winter to spring, enhanced during El Niño periods, frequently reaching annual means higher than 100 g.m-3. Periods from summer to autumn, however, presented lower SPM concentrations, especially during La Niña periods, when the mean annual SPM concentration remained mostly below 50 g.m-3. Seasonal and interannual (ENSO) forcings combined developed configurations of high input periods (HIP) and low input periods (LIP). During the LIP, the river plumes are limited to their tributary zone of influence and the whole lagoon has reduced SPM concentrations. During the HIP, the river plumes spread over the lagoon sub-environments, and the SPM concentrations of all tributaries reach the estuarine zone and the ocean. Thus, the mentioned natural phenomena influence the river plumes spreading, the SPM concentrations in the lagoon, and the export to the Atlantic Ocean in time scales varying from seasonal to interdecadal.